Herpes- Zoster associated Trigeminal Neuritis with Rhombencephalitis: A Rare MRI Presentation - Jagtap, Shubham; Ganeshwala, Uday; Chhabra, Garv (Journal of Neonatal Surgery, 2025)
Trigeminal neuralgia (TN) is characterized by episodic electric, shock-like facial pain. Though often idiopathic, herpes simplex virus type 1 (HSV-1) reactivation can rarely cause symptomatic TN. When the virus affects the brain, it can cause a rare and serious condition called rhombencephalitis. This condition involves inflammation of the rhombencephalon, which includes parts of the brainstem and cerebellum. We report a case of a 74-year-old man with rare MRI findings of both trigeminal neuritis with rhombencephalitis.